2022
DOI: 10.12938/bmfh.2021-046
|View full text |Cite
|
Sign up to set email alerts
|

<i>Clostridium butyricum</i> affects nutrition and immunology by modulating gut microbiota

Abstract: The gut microbiota has nutritional and protective functions. In patients with end-stage renal disease, changes in the gut microbiota disrupt their protective functions. Probiotics help maintain normal bowel function. However, their role in patients with end-stage renal disease is controversial. We investigated whether Clostridium butyricum affects the nutrition and immune function of patients with end-stage renal disease undergoing 3 maintenance dialysis between 2014 and 2015; thirty-seven patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Moreover, we found a higher abundance of Clostridium and a lower abundance of Bacteroides at the genus level in the CB group, which may partially suggest CB colonization. In comparison to patients without CB treatment, the α-diversity index of gut microbiota was more abundant in patients who received CB 50 . Mao et al showed that CB increased the abundance of Bifidobacterium , Lactobacillus , and Lactococcus species in the gut microbiome 51 .…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, we found a higher abundance of Clostridium and a lower abundance of Bacteroides at the genus level in the CB group, which may partially suggest CB colonization. In comparison to patients without CB treatment, the α-diversity index of gut microbiota was more abundant in patients who received CB 50 . Mao et al showed that CB increased the abundance of Bifidobacterium , Lactobacillus , and Lactococcus species in the gut microbiome 51 .…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, we did find a higher abundance of Clostridium and lower abundance of Bacteroides at the genus level in the CB group, which may partially suggest the colonization of CB. In comparison to patients without CB treatment, the α-diversity index of gut microbiota was more abundant in patients who received CB 60 .…”
Section: Discussionmentioning
confidence: 83%
“…It can also use carbohydrates in the large intestine to ferment short-chain fatty acids and repair intestinal mucosa (9, 10). In addition, CB can reduce the PH value of the intestinal environment, inhibit intestinal inflammatory response, and strengthen intestinal immune function and antioxidant capacity (11,12). CB is resistant to most antibiotics (13).…”
Section: Introductionmentioning
confidence: 99%